A new piston referencing algorithm for qualitative assessment of free-piston engine generator performance - Mohd Razali, Hanipah; M. Haziq Adham, Rosli; A. R., Razali (Springer, 2021)
Free-piston engine generator (FPEG) provides a novel method for electrical power generation in hybrid electric vehicle applications. This paper presents a new piston positioning method for assessing the performance of a dual-piston type FPEG. Numerical simulations were conducted to obtain motion profiles necessary for the algorithm development. A flowchart for the algorithm was produced. The new piston referencing is named cyclic position which illustrates similar crank-angle-based referencing employed for conventional crank slider engine applications. The results demonstrated cyclic position as qualitative tool for FPEG performance assessment which can be used for data-acquisition user interface in experimental investigations.